Extraterritorial Application of Human Rights Treaties : Law, Principles, and Policy. - Milanovic, Marko (Oxford monographs in international law., 2014)
States' human rights obligations under international treaties often extend beyond their borders and cases are increasingly being brought for violations which took place outside of a state's territory. This book makes sense of the often confusing case law on this issue and proposes a new way of interpreting extraterritorial human rights obligations.